(untitled) (Global Journal of Human-Social Science, 2022)
This article aims to analyze the conceptions about the teaching of DNA present in the discourse of high school biology teachers and in the Biology Textbooks (BT) of the last National Textbook Plan (PNLD), according to the conceptions of Henri Atlan. The qualitative research used a questionnaire for teachers in the area, and also Biology textbooks for data collection and analysis, in order to answer the following problem situation: What are the concepts of DNA used by teachers and also reinforced by LD for and in Biology teaching ? The data reveal that teachers work with conceptions of DNA teaching as a program the computer, and this concept is also used in Biology textbooks, which presupposes articulating more appropriate terminologies for teaching this molecule due to current studies on epigenetics, in which the complexity of possible combinations of DNA lead to complex and integrative biochemical production. DNA (desoxirribonucleic acid) should be considered a set of complex data, rather than a single and linear program, addressed in the speeches of teachers in the classroom as well as in the adopted textbooks, in a complex notion proposed by Henri Atlan.